2022
DOI: 10.1002/jcc.26888
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights of key host proteins and potential repurposed inhibitors regulating SARS‐CoV‐2 pathway

Abstract: The emergence of pandemic situations originated from severe acute respiratory syndrome (SARS)-CoV-2 and its new variants created worldwide medical emergencies.Due to the non-availability of efficient drugs and vaccines at these emergency hours, repurposing existing drugs can effectively treat patients critically infected by SARS-CoV-2. Finding a suitable repurposing drug with inhibitory efficacy to a host-protein is challenging. A detailed mechanistic understanding of the kinetics, (dis)association pathways, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…With the parallelization of programming codes and advancements in high-performance computing, we can now perform all-atom level molecular simulations for even macromolecular systems, including explicit water molecules. Using classical all-atom molecular dynamics simulations and integrated biased sampling techniques, various studies have reported a deeper understanding of thermodynamics, kinetics, and dissociation pathways for biological molecules [27][28][29][30] , as well as interactions between ligands and proteins, and between nanomaterials and biomolecules 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…With the parallelization of programming codes and advancements in high-performance computing, we can now perform all-atom level molecular simulations for even macromolecular systems, including explicit water molecules. Using classical all-atom molecular dynamics simulations and integrated biased sampling techniques, various studies have reported a deeper understanding of thermodynamics, kinetics, and dissociation pathways for biological molecules [27][28][29][30] , as well as interactions between ligands and proteins, and between nanomaterials and biomolecules 31,32 .…”
Section: Introductionmentioning
confidence: 99%